Effect of CW-GMA welding on the HAZ and mechanical properties of structural steel - Igwemezie, Victor; Musa, Zahraddeen; Ganguly, Supriyo (Springer, 2026)
This work investigated the effect of cold wire gas metal arc welding (CW-GMAW) on the heat-affected zone (HAZ) and mechanical properties of structural steel designated as BS 970 Part 3:1991 080A15 steel. The study involved feeding cold ER70S-6 wire into the welding arc of energised hot wire (HW). Welds were produced at cold wire feed speeds (CWFS) of 2, 4, and 6 m per min labelled CW2, CW4, and CW6, and were compared with conventional welds (CW0) and the parent metal (PM). Metallographic examination, hardness testing, and cross joint tensile evaluation were carried out. Cold wire (CW) addition resulted in a more gradual cooling profile which increased the width of heat-affected sub-zones particularly the grain refined zone (GRZ). Hardness decreased across all weld zones with increasing CWFS indicating improved ductility and reduced potential for brittle phase formation. Although the 0.2% proof stress reduced by about 16% relative to the parent metal (PM), the tensile strength at CW6 approached that of the base material. Ductility loss of 35% in CW0 reduced to 22% in CW welds representing a 13-point improvement. For CW6, the tensile fracture location shifted from the partially transformed zone (PTZ) to the PM close to PTZ region confirming improved mechanical performance. However, at higher CWFS, weld penetration decreased due to reduced arc energy density. The study demonstrates that CW addition can improve ductility and tensile performance in conventional GMA welds while increasing productivity when welding parameters and joint design are optimised.
Keywords: 4014 Manufacturing Engineering; Mining & Metallurgy; 40 Engineering; Cold wire gas metal arc welding; Structural steel; Metallography; Hardness; Tensile testing